Pengaruh Penyuluhan Ibu Hamil Terhadap Pemberian ASI Eksklusif - Melia Puspita Sari; Febi Ratnasari (Universitas Muhammadiyah Surakarta, 2020)
Background: Coverage of breastfeeding in Indonesia in 2015 was only 55.7% and when referring to the 2015 strategic plan target of 39%, nationally the scope of exclusive breastfeeding for infants aged less than 0 to 6 months has met the target. The percentage of exclusive breastfeeding in infants aged 0-6 months in Banten Province in 2016 was 61.6%, a slight increase compared to the percentage of exclusive breastfeeding in 2015 which was only 60.7%. The regency / city with the lowest percentage of exclusive breastfeeding was Pandeglang, which was 19.88%, followed by Serang City at 39.77% (Indonesian Health Profile, 2018). As a result of not providing exclusive breast milk will have an impact on infant health including the incidence of diarrhea, infection and malnutrition. Method: the analytical method used is the method of analysis of journal contents. Readable journals must be read and examined to be clear in analyzing these journals. And an analysis is made of the contents obtained from the research objectives and the results of the research. Searching this literature review through an accredited journal site namely google schoolar, PubMed and using literature from 2016-2020. Results: 67 journals were obtained using keywords and filtered again based on inclusion criteria and obtained literature results that met the requirements of 20 journals. Thus it can be concluded that there is an effect of counseling on pregnant women regarding the administration of colostrum breast milk.